Housing preference among young people: a study from the perspective of university students in Malaysia / Mahazril 'Aini Yaacob, Intan Nursyazwana Makmar Kadapi and Nur Izzaty Hussin - Yaacob, Mahazril 'Aini; Makmar Kadapi, Intan Nursyazwana; Hussin, Nur Izzaty (Research Management Centre (RMC), 2023)
This article aims to investigate housing preferences among young people in Malaysia. This article argues the difference between the supply and demand of homes in this market that needs to be improved, especially on the actual needs of young people. This study utilises a quantitative survey to collect data, and statistical analysis to evaluate the research findings. The study's findings revealed that their housing preference was significantly influenced by factors such as housing price, housing location, housing environment and housing attributes. This research aims to assist housing providers in developing affordable housing that matches potential homebuyers' preferences to avoid property overhangs and offer fundamental guidance to the government for creating housing policies that benefit young people.